Битва під Козацькою Дібровою як фінал протистояння під Конотопом 1659 р. - Осадчий, Є.М. (Праці Центру пам’яткознавства, 2014)
У роботі розглядаються події, що відбулися після поразки московського війська під Соснівкою. На основі архівних і археологічних даних аналізуються дії очільників українського та московського війська. Наводяться маловідомі факти про перебіг битви під с. Козацька Діброва, що відбулися у період відступу московського війська від Конотопа до Путивля. В работе рассматриваются события, имевшие место после поражения московских
войск под Сосновкой. На основе архивных и археологических данных анализируются
действия военачальников украинского и московского войска. Приводятся малоизвестные факты о ходе событий, которые произошли в период отступления московских войск из-под Конотопа в Путивль. This paper analyzes the events that occurred after the under Sosnivka were broken parts cavalry
army of prince Trubetskoy. Based on archival data reproduced the events that occurred during
the crossing over the river Moscow troops Ezuch . Actions analyzed by prince Trubetskoy
organization crossing and further retreat on Putyvl. According miniatures Dutch artist Abraham
van Westerfeld offered reconstruction build Muscovite troops marching on the path of retreat
in Putyvl. Images of the device allows to present the supply train camp Muscovite troops during
his night assault on the Ukrainian-Tatar forces. The data on the losses that were incurred by
both sides during the Battle of Konotop, crossing Ezuch and the Battle of the Cossack Dibrova.
Hostilities under Cossack Dibrova allied forces could not fi nally defeat the army of Prince Alexei
Trubetskoy . Loss of the allied forces did not allow them to continue fi ghting under Putyvl.